A Survey On Ornamental Plants Of Karungal Region, Kanyakumari District, Tamil Nadu, India (International Journal of Food and Nutritional Sciences, 2022)
Herbaceous plant species are important components of ecosystems. Total of 39 angiosperm species in which 72% shrubs, 20% herbs, and 3% trees are present in the Karungal area. The classification of the ornamental flora based on the diversity of the plants can be used as public garden plants. Totally 23 families were identified, among which Apocynaceae (18 %) is the dominant family followed by Rubiaceae, Rosaceae and Asteraceae (6%), Balsaminaceae, Euphorbiaceae, Nyctaginaceae, and Caryophyllaceae (5%), Cupressaceae, Acanthaceae, Zingiberaceae, Heliconiaceae, Araceae, Plumpaginaceae, Asparagaceae, Portulaceae, Melastomataceae, Garryaceae, Papaveraceae, Plantaginaceae, Solanaceae, Lamiaceae and Polemoniaceae (3%). The flowers of most plants have the most attractive potential, although some species also have beautiful fruits and leaves. Even in difficult climatic conditions, particularly water stress, some plants have made morphological, anatomical, and physiological changes to overcome dry conditions.